Some considerations about the process of lexicalization of grammatical units - Karimova, Gulshod (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article discusses changes in the semantic structure of the word, and the process of lexicalization of grammatical units is described on the basis of a comparative analysis of Uzbek and English materials